Unethical behavior in the name of the company: the moderating effect of organizational identification and positive reciprocity beliefs on unethical pro-organizational behavior - Umphress, Elizabeth E; Bingham, John B; Mitchell, Marie S (Journal of applied psychology, 2010)
We examined the relationship between organizational identification and unethical pro-organizational behavior (UPB)-unethical behaviors conducted by employees to potentially benefit the organization. We predicted that organizational identification would be positively related to UPB and that positive reciprocity beliefs would moderate and strengthen this relationship. The results from 2 field studies support the interaction effect and show that individuals who strongly identify with their organization are more likely to engage in UPB when they hold strong positive reciprocity beliefs. Given the nature of reciprocity, our findings may suggest that highly identified employees who hold strong reciprocity beliefs may conduct UPB with an anticipation of a future reward from their organization. Theoretical and managerial implications of our results for understanding unethical behaviors are discussed.